Gastropod Density and Diversity in Tasik Ria Beach Tourism Area, North Sulawesi - Aldi Tharo; Indri S. Manembu; Noldy Mamangkey; Inneke F. M. Rumengan; Medy Ompi; Rosita A. J. Lintang (Sam Ratulangi University, 2025)
Baseline information on intertidal gastropod assemblages is critical for managing tropical shorelines subject to growing recreational pressure. This study quantified species composition, density and diversity of gastropods along the intertidal zone of the Tasik Ria Beach Tourism Area, North Sulawesi, Indonesia. Sampling was conducted once at low tide along three 13 m land‑to‑sea transects spaced 50 m apart. Five 1 × 1 m quadrats were placed at 2 m intervals along each transect. Epifaunal gastropods were hand‑collected, while infaunal taxa were excavated to a depth of 25 cm; all specimens were preserved in 70 % ethanol and identified using regional monographs and the World Register of Marine Species.A total of 24 gastropod species were recorded. Mean densities at the three stations were within ranges typically associated with minimally disturbed sandy‑muddy shores, indicating that habitat remains in comparatively good condition. Shannon–Wiener diversity values (H′) fell within the low‑to‑moderate category, whereas Simpson dominance coefficients (C) were moderate at all stations, reflecting the numerical prominence of Nassarius pullus. The assemblage structure suggests a moderately healthy intertidal community that is beginning to show signs of faunal dominance. Continued periodic recommended to detect potential shifts attributable to intensifying tourism, and to inform evidence‑based coastal management and conservation strategies. Keywords: Gastropods, density, diversity, dominance, and tourist area Abstrak Informasi dasar tentang komunitas gastropoda di zona pasang surut sangat penting untuk mengelola pantai tropis yang menghadapi tekanan rekreasi yang meningkat. Riset ini mengukur komposisi spesies, kepadatan, dan keragaman gastropoda di zona pasang surut Area Wisata Pantai Tasik Ria, Sulawesi Utara, Indonesia. Pengambilan sampel dilakukan sekali saat air surut sepanjang tiga transek darat-ke-laut berukuran 13 m dan berjarak 50 m satu sama lain. Lima kuadrat berukuran 1 × 1 m ditempatkan dengan jarak 2 m di sepanjang setiap transect. Gastropoda yang hidup di permukaan dikumpulkan secara manual, sementara taksa infaunal digali hingga kedalaman 25 cm; semua spesimen diawetkan dalam etanol 70% dan diidentifikasi menggunakan monografi regional dan World Register of Marine Species.Total 24 spesies gastropoda tercatat. Kepadatan rata-rata di tiga stasiun berada dalam rentang yang umumnya terkait dengan pantai berpasir-berlumpur yang minim gangguan, menunjukkan bahwa habitat masih dalam kondisi relatif baik. Nilai keragaman Shannon–Wiener (H′) berada dalam kategori rendah hingga sedang, sedangkan koefisien dominansi Simpson (C) moderat, mencerminkan dominasi numerik Nassarius pullus. Struktur komunitas menunjukkan komunitas intertidal yang sehat namun mulai menunjukkan tanda-tanda dominasi fauna. Pemantauan berkala direkomendasikan untuk mendeteksi pergeseran potensial akibat pariwisata, serta mendukung strategi pengelolaan dan konservasi pesisir berbasis bukti. Kata kunci: Gastropoda, kepadatan, keanekaragaman, dominansi, kawasan wisata.